2022
DOI: 10.1111/bjop.12625
|View full text |Cite
|
Sign up to set email alerts
|

Blunted reward responsiveness prospectively predicts emotional distress when exposed to a naturalistic stressor

Abstract: Both stress and blunted reward responsiveness have been identified as core risk factors of depression. Whether blunted reward responsiveness increases psychological vulnerability to real‐life stress from a dynamic perspective (from stress reactivity to recovery) has not been investigated. By utilizing a real‐world stressful event (i.e. the final examination), this study aimed to explore the role of reward responsiveness in the stress‐emotional distress relationship during stress reactivity and recovery phases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 90 publications
(108 reference statements)
0
5
0
Order By: Relevance
“…The ASR was evaluated after the participants were informed that they would undergo the military physical fitness test the next day. According to previous studies, the examination was a real-world stressful event (e.g., final examination) ( 43 , 44 ), and researchers found that students experienced stress on the day before the final examination ( 44 ). Therefore, the likelihood that the participants included in this study would experience acute stress was very high in the face of the important military physical fitness test.…”
Section: Methodsmentioning
confidence: 99%
“…The ASR was evaluated after the participants were informed that they would undergo the military physical fitness test the next day. According to previous studies, the examination was a real-world stressful event (e.g., final examination) ( 43 , 44 ), and researchers found that students experienced stress on the day before the final examination ( 44 ). Therefore, the likelihood that the participants included in this study would experience acute stress was very high in the face of the important military physical fitness test.…”
Section: Methodsmentioning
confidence: 99%
“…Although we proposed three possible explanations, there were still some findings that might not be fully understood. For instance, some studies appear to show "crossover" or "disordinal" (the key nature of differential susceptibility; see Figure S2 in the online supplemental materials) interaction patterns within their blunted RewP × Stress Exposure findings, but have never explained them from a differential susceptibility perspective (e.g., Feurer et al, 2021;Yan et al, 2023). We call for direct statistical testing of the interaction patterns in the extant and future research and rethinking the role of the RewP based on these corrected analyses.…”
Section: Discussionmentioning
confidence: 99%
“…That is, the blunted RewP is unlikely to be sensitive to the environment, regardless of the type of environment (positive or negative; Dziura et al, 2023). Thus, existing research might misinterpret their blunted RewP × Stress Exposure interactions as diathesis-stress (e.g., Burani et al, 2023; Feurer et al, 2021; Goldstein et al, 2020; Yan et al, 2023), as under the framework of diathesis-stress, the blunted RewP should be vulnerable (or sensitive) to environmental stressors. Accordingly, there might be (at least) three possible reasons that explain the discrepancy between the current results and these previous findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations